2021
DOI: 10.1101/2021.10.08.21264593
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel Investigation of SARS-CoV-2 in COVID-19 Survivors’ Semen in Surabaya, Indonesia

Abstract: The emergence and the widespread of Coronavirus disease 2019 (COVID-19) demands an accurate detection method to establish a diagnosis. Real-time polymerase chain reaction (real-time PCR) is accounted for the perfect point of reference in detecting this virus. The notion that this virus also invades the male reproductive tract requires further investigation to prove the presence of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) in the semen. This investigation was designed to detect SARS-CoV-2 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…The presence of SARS-CoV-2 in semen was assessed by 30 studies (16 cohort, 8 cross-sectional and 6 case series), including 888 patients (1428 specimens). Six studies reported the presence of SARS-CoV-2 in semen (n=14 patients),24–29 but only one followed patients until a negative result was obtained 25…”
Section: Resultsmentioning
confidence: 99%
“…The presence of SARS-CoV-2 in semen was assessed by 30 studies (16 cohort, 8 cross-sectional and 6 case series), including 888 patients (1428 specimens). Six studies reported the presence of SARS-CoV-2 in semen (n=14 patients),24–29 but only one followed patients until a negative result was obtained 25…”
Section: Resultsmentioning
confidence: 99%
“…24 Statistical analysis was performed globally and within each group, respectively, if sufficient. Semen volume, pH, sperm concentration, total, progressive, non-progressive, and immotile motility percentage, morphology percentage, leukocyte, erythrocyte, and immature sperm cells parameters obtained from the current semen analysis were to be statistically compared with individual previous results, which were obtained by Supardi, et al 20 All statistical analyses were performed using SPSS version 25.0. Normality test was based on the result of the Shapiro-Wilk Test.…”
Section: Discussionmentioning
confidence: 99%
“…19 Similar result was found in a prior study conducted in Surabaya, that from 34 men diagnosed with infertility in the resolution phase of COVID-19 infection, one of them showed positive results in seminal SARS-CoV-2 PCR, after 121 days since diagnosis of COVID-19 based on nasopharyngeal PCR swab. 20 Longer-term effects of COVID-19 on males have also been reported in several case reports. A 36 years-old man with no history of any kind of infertility pre-COVID-19 was diagnosed with oligoasthenoteratozoospermia one month post-COVID-19, only improving after four months post-COVID-19 without reaching pre-COVID-19 semen analysis values.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations